2019
DOI: 10.1186/s12885-019-5967-8
|View full text |Cite
|
Sign up to set email alerts
|

Circ-Foxo3 is positively associated with the Foxo3 gene and leads to better prognosis of acute myeloid leukemia patients

Abstract: Background The Foxo3 gene, belonging to the forkhead family, is one of the classes of transcription factors characterized by a forkhead DNA-binding domain, which usually considered being a cancer suppressor gene. Circ-Foxo3 is a circular structure which connects the 3’end to the 5’end. Scholars detected that circ-Foxo3 could compete with Foxo3 for binding to some miRNAs. Methods In this study, we will test the expression of Foxo3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Few studies have investigated circRNA expression in myeloid malignancies. In acute myeloid leukemia (AML), a role for circRNAs in the regulation of cell proliferation and leukemogenesis ( Guarnerio et al, 2016 ; Sun et al, 2019 ; Yi et al, 2019 ), in drug resistance ( Shang et al, 2019b ; Cao et al, 2020 ), and as a diagnostic biomarker ( Zhou et al, 2019 ) has been reported. Furthermore, mounting evidence suggests a role as potential therapeutic targets ( Conn et al, 2015 ; Hirsch et al, 2017 ; Wu et al, 2018b ; Bell et al, 2019 ; Shang et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated circRNA expression in myeloid malignancies. In acute myeloid leukemia (AML), a role for circRNAs in the regulation of cell proliferation and leukemogenesis ( Guarnerio et al, 2016 ; Sun et al, 2019 ; Yi et al, 2019 ), in drug resistance ( Shang et al, 2019b ; Cao et al, 2020 ), and as a diagnostic biomarker ( Zhou et al, 2019 ) has been reported. Furthermore, mounting evidence suggests a role as potential therapeutic targets ( Conn et al, 2015 ; Hirsch et al, 2017 ; Wu et al, 2018b ; Bell et al, 2019 ; Shang et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA-DLEU2 serves as an oncogenic circRNA in the AML progression via promoting PRKACB expression (29). Circ-Foxo3 is in positive association with the Foxo3 gene expression and its high expression contributes to a better prognosis of AML patients (30). In this study, we rst proved that circ_0000005 expression was greatly elevated in AML.…”
Section: Discussionmentioning
confidence: 68%
“…Circ-Foxo3 might be a promising biomarker for the prognosis and treatment of AML. 233 In addition, some circRNAs might be related to drug resistance in acute myeloid leukemia. For example, silence of circPAN3 significantly restored drug sensitivity to ADM in the two ADM-resistant cell lines, and overexpression of circPAN3 had the opposite effect.…”
Section: Myeloid Leukemiamentioning
confidence: 99%